Pengaruh Kualitas Layanan Terhadap Implementasi SIMRS dengan Penggunaan Sistem dan Struktur Organisasi Sebagai Variabel Intervining - Rizkiyatul Amalia; Angga Ferdianto (Jurnal Rekam Medis dan Informasi Kesehatan, 2022)
SIMRS implementation aims to help improve the quality of services provided by hospitals to increase patient satisfaction. Service quality is one of the obstacles in the implementation of SIMRS provided by service providers which has an impact on the use of information systems and SIMRS implementation. The purpose of this study was to determine the effect of service quality on the implementation of SIMRS using the HOT– Fit method. This study used a cross-sectional design with a population of 288 people and the sample used was 167 people who used SIMRS. Multivariate analysis test using SEM analysis technique with Smart Partial Least Square (Smart PLS) application. The test results show that there is no influence between service quality on system use and system use on SIMRS implementation (P-values 0.912). There is an influence between service quality on organizational structure (P-Values 0.021), organizational structure on system use (P-Values 0.037), and organizational structure on SIMRS implementation (P-Values 0.000). The use of the system can be an intervening variable between service quality and SIMRS implementation. However, the use of the system is not capable of being an intervening variable between service quality on implementation and organizational structure on SIMRS implementation.